Literature Review: The benefits of occupational health and safety management systems implementation for the safety of workers - Mulyawati, Sita Dewi; Setyaningsih, Yuliani; Denny, Hanifa Maher (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: The construction sector is of particular concern with regard to occupational safety and health, given the persistently high incidence of accidents and safety risks. In 2021, there were 234270 cases of work-related accidents, underscoring the urgent need for the implementation of an effective occupational health and safety management system (OHMS) to protect workers and mitigate the risks associated with injuries and accidents.Objectives: This study aims to investigation is to ascertain the advantages of implementing an OHSMS in the construction sector, with a particular emphasis on worker safety.Methods: A literature review in this study employed online databases, including SINTA, Google Scholar, and Garuda. The keywords utilized were "safety culture," "OHS," and "safety management system" in the construction industry. The inclusion criteria were articles published within the last five years (2020-2024), research conducted in Indonesia, and the research population comprising construction sector workers.Results: The implementation of OHSMS in the construction sector has been demonstrated to significantly reduce the incidence of work-related accidents and injuries, while simultaneously enhancing the efficiency of construction projects. The effectiveness of the construction sector work system is contingent upon a number of factors, including the level of awareness among workers regarding safety protocols, their mindset, and the budgetary allocation towards ensuring the safety and health of workers in the construction sector.Conclusion: The findings of this study also revealed that the implementation of an OHSMS in the construction sector can effectively reduce accidents and enhance project efficiency. However, the field-level adoption of such systems is still constrained by various factors, including worker awareness and capital expenditure.